Analisis kemampuan mahasiswa dalam mengembangkan penilaian kinerja keterampilan menulis dalam pembelajaran bahasa Indonesia di sekolah dasar - Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2025)
This study aims to: (1) determine students' understanding of the concept of performance assessment in Indonesian language learning, and (2) assess students' ability to develop performance assessment instruments in Indonesian language learning in elementary schools. This research is a descriptive study using a qualitative approach. The subjects of this study were 80 students from the Elementary School Teacher Education program at FKIP UNS. Data collection techniques used were documents, tests, and questionnaires. The credibility of the data was ensured through triangulation. The data obtained were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The study concluded that (1) the understanding of PGSD FKIP UNS students regarding the concept of performance assessment was very good, with 90% of students answering correctly and 10% answering less accurately, and (2) the students' ability to develop performance assessments at the planning stage was quite good, with an average score of 75.